Disclosure of myelodysplastic syndrome diagnosis: improving patients' understanding and experience. (9th January 2013) - Besson, Caroline; Rannou, Sandrine; Elmaaroufi, Hicham; Guirimand, Nicolas; Tresvaux du Fraval, Frédéric; Cartron, Laure; Jenny, Sarah; Festy, Patrick; Fenaux, Pierre; Leplège, Alain
Abstract Purpose How a diagnosis of cancer is disclosed can affect psychological morbidity. Haematological malignancy specialised terminology may make the disclosure difficult. We analysed how disclosure of a diagnosis of myelodysplastic syndrome (MDS) is experienced by patients. Methods Patients from the French MDS support group were questioned about their demographic and clinical characteristics, diagnosis disclosure circumstances as well as experiences and expectations. After a phase test, a written questionnaire was sent to the 150 members of the support group. Results Of the 73 patients who returned a useable questionnaire, disclosure had been experienced negatively by 32 patients (45%). Only 53% of those patients were satisfied with the information provided compared with 80% of those who had positive/neutral feelings (P = 0.02). Overall, patients felt they should have been given fuller information at the time of disclosure. In retrospect, almost all patients (94%) thought that comprehensive, accurate information should be provided at disclosure, even if the truth might be hard to cope with. Patients reporting not having been given satisfactory information complained about a lack of perspective (3) or clarity (7), eight (11%) mentioned cancer during the interview, and four explicitly expressed that this word should be more frequently used. Conclusion Many patients had experienced disclosure negatively, frequently finding that the information provided had been insufficient and feeling that MDS was not well understood as a disease. Haematologists disclosing diagnosis to patients with a blood malignancy may benefit from following the same guidelines as oncologists in delivering comprehensive, understandable information.